1997
DOI: 10.1073/pnas.94.11.5955
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a divergent expansin gene is fruit-specific and ripening-regulated

Abstract: Expansins are proteins that induce extension in isolated plant cell walls in vitro and have been proposed to disrupt noncovalent interactions between hemicellulose and cellulose microfibrils. Because the plant primary cell wall acts as a constraint to cell enlargement, this process may be integral to plant cell expansion, and studies of expansins have focused on their role in growth. We report the identification of an expansin (LeExp1) from tomato that exhibits high levels of mRNA abundance and is specifically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
248
1
7

Year Published

1998
1998
2010
2010

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 367 publications
(264 citation statements)
references
References 40 publications
(46 reference statements)
8
248
1
7
Order By: Relevance
“…Expansins are proteins that are thought to disrupt the noncovalent association between cellulose and matrix polysaccharides and could act to regulate noncovalent cell wall polymer associations in ripening fruit. Rose et al (1997) recently identified and characterized a highly abundant, fruit-ripening-specific expansin gene from tomato, as well as homologs from strawberry and melon. The role of expansins in fruit softening is not clear and is currently under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Expansins are proteins that are thought to disrupt the noncovalent association between cellulose and matrix polysaccharides and could act to regulate noncovalent cell wall polymer associations in ripening fruit. Rose et al (1997) recently identified and characterized a highly abundant, fruit-ripening-specific expansin gene from tomato, as well as homologs from strawberry and melon. The role of expansins in fruit softening is not clear and is currently under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Pc-Exp7 (Hiwasa et al 2003) and the novel Md-Exp7 are phylogenetically grouped close to Le-Exp1 (Fig. 8), a tomato expansin gene that is fundamental for fruit softening (Rose et al 1997). …”
Section: Md-exp7 Functional Markermentioning
confidence: 94%
“…Expansins, a novel class of proteins, have been proposed as the major enzymatic agent in cell-wall remodelling (Cosgrove 2000b) and are thought to be involved in the disruption of the non-covalent bonds between the hemicellulose matrix and the cellulose microfibril (Cosgrove 1997), thus exposing the structural polymer to the action of other cell-wall enzymes. Recently, a two-step fruit softening model has been defined in which expansin acts in the early stage and the latter is regulated by hydrolases like polygalacturonases (Rose et al 1997;Powell et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that the LeEXP18 expression does not correlate with elongation growth and that some of the tomato expansin genes are differentially expressed during fruit development, suggesting that not all the expansins are involved in the expansion process (Brummell et al, 1999a(Brummell et al, , 1999bCaderas et al, 2000;Rose et al, 2000). Therefore, the complexity of the expansin family and the tissue-specific expression patterns of some of its members suggest that different expansins may play different roles in various cell types during organ development in plants (Rose et al, 1997;Reinhardt et al, 1998).…”
mentioning
confidence: 99%